A simplified method to estimate the soil-water characteristic curve - Chin, Kheng Boon (2011)
This paper proposes a simplified method to estimate the soil-water characteristic curve (SWCC) for both coarse- and fine-grained soils using one-point SWCC measurement and basic index properties. Parameters of the Fredlund and Xing SWCC equation were correlated with the basic properties of 60 soils: 30 soils each of coarse- and fine-grained types. Sensitivity analysis revealed that the location of the one-point measurement at matric suctions of 10 and 500 kPa gave the most reliable SWCC using the proposed method for coarse- and fine-grained soils, respectively. The validity of the proposed method was evaluated using a total of 62 soils collated from published literature with 31 soils each of the coarse- and fine-grained types. The proposed method gives a good estimation of the SWCC and uses fewer parameters when compared with existing one-point SWCC estimation methods.